The susceptibility of pectinids larvae to farming conditions : open flow as an alternative to mass mortalities - Holbach, Marine (HAL CCSD, 2014)
In many countries, aquaculture of pectinids depends on the success of artificial spat production in hatchery. This production is always unpredictable due to the variability of hatching rate and larval survival. Flow-through larval rearing systems were developed in Norway for the King scallop Pecten maximus and showed promising results. Unfortunately the system needs to be optimized since the larval yields and the densities used are still relatively low. In France, a small-scale (5 L) and high-density (≤ 300 larva mL-1) flow-through larval rearing system was successfully developed for oysters. First trials in such system and in similar conditions with P.maximus failed as we registered slower growth and high mortality rate in only a few days. It is known that pectinids larvae are more sensitive to environmental conditions than the oyster Crassostrea gigas, for example.Nowadays, it is important to identify and to understand the phenomena disturbing larval development in flowthrough system to improve larval quality and production yields. This doctoral project provided some indications how improving P. maximus flowthrough rearing system while limiting the use of antibiotic through a better understanding the physiological mechanisms involved in the larval response to a stressful environment Dans de nombreux pays, l’aquaculture de pectinidés dépend aujourd’hui du succès de la production contrôlée de juvéniles. Néanmoins, les fortes variations des taux d’éclosion des oeufs et de la survie larvaire, enregistrées à ce jour, rendent cette production imprévisible. Les élevages larvaires en flux ouvert de coquilles Saint-Jacques (Pecten maximus) ont été développés en Norvège et présentent des résultats prometteurs. Malheureusement, les rendements de production encore faibles et l’impossibilité de travailler à fortes densités restent un frein majeur au développement de cette technique. En France, une technique en flux-ouvert, en petit volume (5 L), et à forte densité (≤ 300 larves mL-1) a été développée pour les ostréidés. ...